PROVENANCE AND TECTONIC SETTINGS OF ACCRETIONARY WEDGE SEDIMENTS ON NORTHEASTERN KARAGINSKI ISLAND (KAMCHATKA, RUSSIAN FAR EAST) - Ledneva G.V.; Garver J.I.; Lederer J.; Hollocher K.T.; Shapiro M.N.; Brandon M.T. (My University, 2004)
The provenance and tectonic setting of the sediments and rare cobbles from the accretionary wedge on Karaginski Island were examined. This study provides a picture of the nature of the NE Asian paleomargin in the middle Eocene to early Miocene. The trace element geochemistry of shale from the flysch and mélange indicates (a) their common provenance with the quartzofeldspathic and arkosic sandstones, and (b) derivation of these sediment types from active continental and island arcs with partially dissected basement rocks. Previous studies of the sandstones [Shapiro et al., 2000] showed that they dominate in debris whose composition is very similar to those of the felsic extrusive and intrusive rocks in cobbles and boulders embedded in the sediments. Fission-track (FT) ages from detrital zircon from sandstones, and felsic cobbles show their derivation from sources with several cooling histories in the Late Cretaceous and Early Tertiary. The youngest detrital component probably represents continuous younging population from active volcanism in the source that is nearly the same age of deposition. The felsic cobbles represent the essentially random selection of the older material component. They include three distinct types: (a) subduction-related low-K tonalites and trondhjemites and their extrusive analogues; (b) crustally-derived med-K two-mica leucogranites, and (c) crustally-derived high-K biotite leucogranites. The felsic rock cobbles of all types have a narrow range of zircon FT grain ages that indicate cooling in the source in the Late Cretaceous to Early Paleogene. Tonalites and trondhjemites (low-K) cooled at 53.8 ( - 3.5/+3.8) Ma and 78.5 ( - 6.7/+7.6) Ma. The rhyolites (med-K) cooled at 70.1 ( - 3.7/+3.9) Ma. The biotite leucogranites (high-K) cooled between 59.1 Ma ( - 3.3/+3.9) and 58.6 ( - 3.2/+3.3) Ma (two clasts). The Late Cretaceous cooling ages (70-78 Ma) probably reflect original magmatic activity whereas the Early Eocene cooling ages may indicate timing of exhumation. The chemical and age data obtained on the felsic cobbles suggest derivation of the accretionary wedge sediments from a source formed either by: (a) subduction in the Late Cretaceous and collision/exhumation in the Early Paleogene; or by (b) continuous subduction. The closest petrochemical and age intrusive and extrusive analogues of the felsic cobbles occur only locally in the Olyutorsky Peninsula subterrane. Nonetheless, this structure is too small and too remote from Karaginski Island to supply enough material for the middle Eocene-early Miocene accretionary wedge sediments. We speculate that the structure of the Olyutorsky Peninsula subterrane might be extended in the shelf where several highs exist.
Keywords: SHALE; FELSIC CLASTS; FISSION-TRACK DATING; PROVENANCE; ACCRETIONARY WEDGE; KAMCHATKA; Cretaceous; Miocene; Eocene; Mesozoic::Cretaceous; Кайнозой::Палеоген::Эоцен; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Miocene; Мезозой::Меловая; Cenozoic::Paleogene::Eocene